Preventing infectious diseases in Santa Cruz, Bolivia: two years of successful management of medical waste through PROSALUD - Jose Luis Aramayo (The Journal of Infection in Developing Countries, 2007)
Santa Cruz is one of Bolivia's fastest growing cities and its problems include population growth, poverty, deficient basic services, a lack of drinking water, limitations in the treatment of wastewater, inadequate management of solid waste, deficient housing conditions, malnutrition, and under-nourishment. Working with the non-profit organization PROSALUD, I have contributed to several improvements in solid waste management in order to decrease the transmission of intrahospital infections.